2019
DOI: 10.1111/hepr.13362
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy of elbasvir and grazoprevir for hepatitis C virus (genotype 1): A nationwide, multicenter study by the Japanese Red Cross Hospital Liver Study Group

Abstract: Aim The present study aimed to determine the real‐world efficacy and safety of the non‐structural protein (NS)5A inhibitor elbasvir (EBR) combined with the NS3/4A protease inhibitor grazoprevir (GZR) in patients with hepatitis C virus (HCV) genotype 1 (GT1) infection. Methods This study retrospectively evaluated the rate of sustained virologic response at 12 weeks post‐treatment (SVR12) and the safety of EBR/GZR treatment in 159 men and 194 women with a median age of 72 years, and it assessed factors associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
(45 reference statements)
0
21
1
Order By: Relevance
“…In this study, side effects were reported in 39 patients. Although the reported AE incidence in this study was only slightly higher than that in some real-world studies [15,16], most of AEs were mild in severity. During treatment, the hyperbilirubinemia observed was the most common adverse event; however, the severity was mainly graded 1 or 2 and lasted only 2-4 weeks for most patients.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…In this study, side effects were reported in 39 patients. Although the reported AE incidence in this study was only slightly higher than that in some real-world studies [15,16], most of AEs were mild in severity. During treatment, the hyperbilirubinemia observed was the most common adverse event; however, the severity was mainly graded 1 or 2 and lasted only 2-4 weeks for most patients.…”
Section: Discussioncontrasting
confidence: 81%
“…Epidemiological studies reported that HCV genotype 1 infection was the most prevalent genotype in the world and China [11][12][13]. As a powerful antiviral regimen for HCV-1b has been demonstrated in clinical studies, there are several reports on the outcomes of EBR /GZR treatment in real-world clinical practice [14][15][16]; however, there are few reports from the Chinese mainland. Chinses patients in the real world are more heterogeneous and have more complications comparing with those in RCT studies, and there are differences in viral infection pathways, races from other countries such as Europe and the United States, therefore, it is worthwhile for us to discuss the real effect of this regimen on hepatitis C patients in China.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous report on the survey on the etiologies of LC revealed that the contribution of viral hepatitis remarkably decreased, and the ratio of HCV-related LC dropped to < 50% after 2014. We considered that this was due to recent advances in treatment for viral hepatitis [ 13 – 18 ] and official measures that are provided in Japan such as the financial support system for patients to receive antiviral treatment [ 5 , 6 ]. However, in the current study, viral hepatitis was shown to remain a major cause of HCC in Japan, although the contribution had gradually decreased during the recent decade.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent reports showed that the coexistence of NS5A and NS5B RAS was associated with SOF/LDV treatment failure . Some reports showed that the coexistence of NS5A was associated with DAA treatment failure . Uemura et al .…”
Section: Discussionmentioning
confidence: 90%